(untitled) (Revista de Artes Marciales Asiáticas, 2015)
Martial arts can be defined as history in motion. Few sport activities of international fame represent a complex symbolic and practical repertory of ethic morality and aesthetic sensuality so distinctive of a nation as the Korean martial disciplines do, especially taekwondo and gumdo. Similar to other combat sports the martial arts gym (dojang) is the place where values are produced and reproduced and where the appropriation of skills, cognition and recognition – degrees, certificates, and so on – that legitimates the social and bodily devotion of an individual to a martial art takes place. This article aims to transmit the emotions generated in a neophyte by the practice of a martial art and the social and kinaesthetic strains that result from this action in modern Korean society. It also explores some of the historical factors linked to its development and rapid expansion, in barely half a century.